A Design of Web 2.0 Technology to Support Students in Guidance and Counseling Services - Septiani, Pipit; Astuti, Budi (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to develop Web 2.0 Technology, which is used to help the process of guidance and counseling on students. The industrial revolution 4.0 is an era where the development of technology is very influential in various fields, especially in guidance and counseling in schools. Guidance and Counseling teachers are required to develop their potential in guidance and counseling technology services. There are various kinds of technologies that can be used by guidance and counseling teachers; one of the technology is Web 2.0. Web 2.0 technology is a platform where students can interact, share, create, and so on. In this research, web 2.0 technology is designed in the form of a website with various features such as virtual counseling services, career analysis, interactive material about life, and so on. This study uses a research and development method, which is currently at the planning stage. Hopefully, through web 2.0, technology can make effective counseling and guidance services at this time. Background of study: Guidance and Counselling Aims and scope of paper: Emerging Technology for Counseling Service, Cyber Counseling Methods: RnD (Planning Stage) Result: Design of Web 2.0 Conclusion: Hopefully, through web 2.0, technology can make effective counseling and guidance services at this time